A model for implementing oral health-promoting school: Integration with dental students' educational curriculum: A protocol study - Bahareh Tahani; Imaneh Asgari (Wolters Kluwer Medknow Publications, 2022)
BACKGROUND: Schools are ideal setting for children's oral health-promoting programs. It is an integrated model for oral health-promoting schools (OHPS) with the capacities of dental school's curriculum and dental students as workforces. In this protocol, the principle of planning and implementation of the oral health program is described. MATERIALS AND METHODS: Based on the PRECEDE-Policy, Regulatory, and Organizational Constructs in Educational and Environmental Development (PROCEED) planning model, a framework for determining the potential predisposing, reinforcing, and enabling factors that could be intervening was diagnosed. To adapt the phases of the planning model for integration of the "OHPS" principles and the dental students' curriculum, the following steps are supposed to be considered: Phases 1-5 which are to assess the baseline data will include the assessment of children oral health status and parents and teachers' knowledge, attitude, and performance. Phase 6 or implementation phase will be allocated to oral health education interventions for students, parents, and teachers, professional screening, prevention, and referral. Phase 7 or the process assessment phase will be to record the number of screened students, the amount of fissure sealant and fluoride provision, and percentage of trained parents and teachers. Phase 8 or the impact assessment phase will assess the students' improvement in knowledge and practice, decayed, missing, and filled teeth scores, teachers and mothers' oral health attitudes and behaviors, and brushing and flossing behaviors. At the last, cost analysis of the program and long-term monitoring of the interventions is suggested. CONCLUSION: In case that the effectiveness of this model is proven, it can be implemented by other dental schools for the primary schools in their regions. Considering the number and distribution of dental schools in the country, this model is executable as targeted population oral health promotion approach in 6-12-year-old schoolchildren.